DIPG-21. DIPG cells alter the permeability of the blood-brain barrier in the brainstem leading to treatment failure. (3rd June 2022) - Ung, Caitlin; Upton, Dannielle H; Venkat, Pooja; Pandher, Ruby; Curnis, Flavio; Corti, Angelo; Nicolazzo, Joesph; Mayoh, Chelsea; Tsoli, Maria; Ziegler, David S
Abstract: Diffuse Intrinsic Pontine Glioma (DIPG) is an aggressive paediatric high-grade glioma with no effective therapies. The blood-brain barrier (BBB) presents a significant obstacle for delivery of therapeutics into the brain, especially in the brainstem. This study aims to investigate the effect of DIPG cells on the BBB in the brainstem. We hypothesized that the location of DIPG may result in a less permeable BBB than other brain regions. We compared two independent orthotopic models with the same DIPG cells injected in the cortical region or brainstem. We found that treatment with mTOR inhibitor, temsirolimus, significantly extended survival for cortical tumors compared with the same tumor in the brainstem (p=0.0097). Immunohistochemical analysis showed significant reduction of mTOR target, P-p70S6K, in the cortical region compared to brainstem in treated animals, with pharmacokinetic analysis confirming significantly higher temsirolimus levels in the cortical region. These findings suggest that cortical tumors respond better than brainstem tumors, and that a less permeable BBB in brainstem tumors contributes to treatment failure. To understand whether DIPG cells affect the BBB in the brainstem, single-cell RNA sequencing experiments were conducted on vasculature isolated from DIPG and matrigel-injected mice. Gene-ontology overrepresentation analyses identified downregulation in the P38MAPK pathway in endothelial cells from DIPG-injected mice, suggesting the potential for therapeutic manipulation with cytokines. Treatment with SNGR-TNFα, a derivative of an agent successfully used in improving drug penetration in CNS lymphoma patients, in an in vitro BBB/DIPG model significantly reduced transendothelial resistance, and further exploration into the effects on the BBB in vivo is currently being undertaken. Our studies indicate that the intact BBB in the brainstem in DIPG is a major reason for treatment failure, and DIPG cells directly influence the vasculature and response to treatment. This may lead to a novel DIPG treatment strategy and for other brain tumors.